Corporate governance and director's remuneration : some evidences from small Malaysian listed companies - Nyambwa, Husna Siraji (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2014)
Over the past few years, the executive remuneration has increased rapidly and has attracted the interest of academics, public media as well as policy makers due to well-known market failure at the heart of corporate governance regime. Particularly, weak corporate governance (CG) mechanism contributes to the financial crisis and has drawn attention to the high levels of executive compensation. The problem arises how corporate governance mechanism resolves the conflict of interest between shareholders and directors as well as improving company performance. The problem is worst in the small firms because many of the small firms are owner-controlled. This study extensively investigates the effects of different aspects of corporate governance mechanism, including–board size, board shareholding, CEO duality, family member, independent directors in remuneration committee, and number of board meeting, on executive remuneration in small firms listed on Bursa Malaysia. The firm characteristics such as, performance (ROA) and opportunity growth (TOBIN Q) were controlled for. The final sample of this study consists of 173 bottom listed companies from Bursa Malaysia based on market capitalization in year 2010. The Ordinary Least Squares (OLS) regression was used to estimate the relationship between remuneration as dependent variable and other independent variables. A finding from this study reveals that, there is significant positive relationship between executive ownership and executive remuneration. Furthermore, this study reveals that, there is significant positive relationship between board size and executive remuneration. Moreover, the family member shows a significantly positive relationship with remuneration. The results provide evidence that the family members manipulate power and control remuneration in small firms. Also there is significant positive relationship between independent directors in the remuneration committee and directors remuneration. This indicate that in the small firm the independent directors are not truly independent to monitor and control the firm activities, including minimising the excessive remuneration. The results indicate corporate governance system of small firm cannot improve firm performance rather grant executive high compensation. Thus, characteristics in determining remuneration in small firm have been found to facilitate executive needs rather than to attempt to monitor them. Therefore this study contributes to the rising literature on executive directors' remuneration manipulating boardroom pay especially for bottom listed companies in Malaysia.